Chronicle of international labor jurisprudence. January / june 2017 - Arias Domínguez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In the reference period, there are no new “open” or “pending” complaints before the Committee on Freedom of Association. Neither the reports: no. 381 (329th meeting, Geneva, 9-24 March 2017); and No. 382 (330th meeting, Geneva, June 17, 2017) of the Freedom of Association Committee, referenced singular problems about the Kingdom of Spain.The Court of Justice of the Union has issued two resolutions that directly affect to Spain: Rodrigo Sanz on working conditions in Public Universities, and Pérez Retamero on working time in mobile or itinerant activities. Reference is also made, although it does not affect Spain directly, the Asma Bougnaoui case because of the importance for our labor legal system of its doctrine on the use of Islamic headscarves in work centers. In the area of the ECHR, labor-related resolutions affecting Spanish citizens have not been issued during the reference period.
Keywords: Professor in Public University interim civil servant; Reduction of working day due to budgetary reasons; Discrimination in relation to career public officials; .Mobile or itinerant workers; Inadmissibility of the Community reference for a preliminary ruling; Use of the Islamic handkerchief in work places; Discrimination for religious reason